PENGARUH ZPT TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS JAGUNG MANIS (Zea mays L.) DI LAHAN SALIN - Rima Rizka Arozza Matondang (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of zpt on the growth and production of some sweet corn varieties in the saline field. This research was conducted in May until July 2017. The research used factorial randomized block design with 15 treatments and 4 replications. The parameters observed were plant length, number of leaves, flowering age of male and female, length of cob, number of cobs of crop, weights of cob and weight of 100 seeds per plot. The results showed that the observation of varieties treatment was significantly different to the height of tanama (cm) and weight of 100 seeds (gram). Observation of the treatment of ZPT Atonik and Novelgro Alpha was significantly different to the parameters of plant height (cm), number of leaves (strands), harvest age, cob length (cm) and cob weight (gram). The observation of interaction treatment between varieties and ZPT Atonik and Novelgro Alpha had significant effect on plant height (cm), number of leaves (strands), number of cobs, gram length and gram weights.